The Theory and Practice of Islamic Terrorism
IX, 255 p.
Keywords: This is the first anthology designed to enhance the reader's understanding of the multiple dimensions of Islamic terrorism by presenting a cross-section of recent articles and selections from cutting-edge books on the subject.